Chemotherapy and chemoembolization of patients with oncopathology as a risk factor for the development of myocardial dysfunction - Saule Kubekova; Natalya Zagorulya; Yelena Ryb; Niyaz Malayev; Aruzhan Abdilda (National Scientific Medical Center, 2023)
Considering the aging of the population, the combination of cardiovascular diseases with oncopathology is gaining more relevance. Liver cancer occupies the 6th place in the structure of the incidence of neoplasms and the 3rd place in mortality from all oncological diseases. One of the main methods of treating patients with liver cancer is chemotherapy and chemoembolization, which significantly affect the myocardium, developing cardiotoxicity. Myocardial damage is reflected in the development of heart failure, which subsequently is the main cause of death in cancer patients.